Alternative splicing regulates PACC1 function and promotes acidosis-induced cytotoxicity - Tamburro, Serena; Gorrieri, Giulia; Callegari, Niccolò; Guida, Floriana; Antonini, Francesca; Musante, Ilaria; Baldassari, Simona; Zara, Federico; Scudieri, Paolo (Frontiers in Cell and Developmental Biology, 2026)
IntroductionPACC1 (also named TMEM206) encodes a proton-activated chloride channel implicated in acid-induced cell death, but its tissue distribution, cellular expression, and isoform-specific roles are incompletely understood.MethodsWe mapped PACC1 expression and splicing across normal human tissues, with emphasis on the central nervous system, using RNAscope in situ hybridization, quantitative cell-type-specific co-detection, RT-PCR, and isoform-specific in situ probes. Functional properties of PACC1 splice variants were assessed by reconstituting each isoform in PACC1-deficient cells.ResultsPACC1 was broadly expressed across tissues, with especially high and uniform expression in the brain. Quantitative analyses revealed PACC1 localization in both neurons and astrocytes, with higher abundance in astrocytes. Two major splice variants, PACC1-V1 and PACC1-V2, were investigated, distinguished by exon 2 inclusion and exhibiting distinct tissue and developmental expression patterns. Functional assays indicated isoform-specific differences: PACC1-V2 predominantly localized to endosomes and prevented endosomal hyperacidification, whereas PACC1-V1 accumulated at the plasma membrane and enhanced acid-induced cell death.ConclusionAlternative splicing governs PACC1 channel trafficking and function. Isoform-specific behavior suggests distinct roles for PACC1 variants in cell development and responses to acid stress, particularly within the nervous system.